Crop wild phylorelatives (CWPs): phylogenetic distance, cytogenetic compatibility and breeding system data enable estimation of crop wild relative gene pool classification. (10th September 2020) - Viruel, Juan; Kantar, Michael B; Gargiulo, Roberta; Hesketh-Prichard, Peri; Leong, Nathan; Cockel, Christopher; Forest, Félix; Gravendeel, Barbara; Pérez-Barrales, Rocío; Leitch, Ilia J; Wilkin, Paul
Abstract: Enabling food security requires access to a broad range of genetic resources to facilitate crop breeding. This need is increased in a climate change scenario, which will require the production of novel crops adapted to new conditions. However, many major crops have reduced genetic diversity due to the genetic bottlenecks that they have experienced during their domestication and subsequent breeding. Crop wild relatives (CWRs) remain underexploited in plant breeding programmes, mostly because of the lack of knowledge of their cross-compatibility with crops. In this study, we use a combination of phylogenetic distance metrics, cytogenetic compatibility data (e.g. chromosome number and ploidy) and information about breeding systems to predict interspecific cross-compatibility between crop and wild species and hence identify crop wild phylorelatives (CWPs) (i.e. CWRs that can breed with the crop). We illustrate this concept using cultivated asparagus as a model by integrating previous cross-compatibility knowledge and CWR classifications into a phylogenetic framework reconstructed using available sequence data. Our approach aims to reinforce the use of the gene pool classification system of CWRs of Harlan and De Wet, since CWPs are estimated to belong to the secondary gene pool and non-CWPs to the tertiary gene pool. Identifying CWPs unlocks novel uses of genetic resources, although such data are available for less than half of the known CWRs (43.4% with sequence data and 32.5% with known ploidy). The need to conserve plants that provide or enhance provisioning ecosystem services, including CWRs, is clear if we are to rise to the global challenge of ensuring food security for all. However, basic knowledge about their conservation status is still lacking, with only c . 20% of CWRs assigned an IUCN red list assessment, 23% of which are Data Deficient (DD). Using the CWP classification presented here to define CWRs will contribute towards helping to prioritize CWRs for IUCN assessments and, where prioritised, conservation.